SOLUTIONS OF OVERCOMING FEAR TO SPEAK BEFORE PUBLIC (Scientific journal of the Fergana State University, 2024)
The article is devoted to reflections on the main causes of storong anxiety , fear and loss themselves in the speech process, which is the main introductory problem in the art of public speaking, and alternative solutions to these shortcomings. Empirical researches show that approximately 77% of people suffer from fear of public speaking. This means that ¾ of the world is closely related to this problem.In general, it is possible to create a sense of overcoming fears by cleaning up the emotional residue of a traumatic event. Practicing, preparing, believing in yourself, and facing your fears through speech can help you and enhance your ability to speak confidently.In addition, overcoming the fear of speaking before the public is possible with the right strategies and mindset. By preparing thoroughly, visualizing success, practicing relaxation techniques, starting small, using positive self-talk, seeking support, and embracing mistakes, you can gradually build confidence and overcome your fear. Remember that it takes time and practice, but with dedication and perseverance, you can become a confident and effective public speaker. Don't let fear hold you back from sharing your message and engaging with your audience. Take the first step, and you'll be amazed at what you can achieve.